Inhibiting ADAM17 enhances the efficacy of olaparib in ovarian cancer spheroids - Christoph Rogmans; Jan Dittrich; Emily Hamm; Jörg Paul Weimer; David Holthaus; Norbert Arnold; Inken Flörkemeier; Nicolai Maass; Peer Jansen; Astrid Dempfle; Dirk O. Bauerschlag; Nina Hedemann (Scientific Reports)
Abstract Acquired or de novo resistance to poly (ADP-ribose) polymerase inhibitors (PARPi) is a major challenge to ovarian cancer treatment. Therefore, strategies to overcome PARPi resistance are critical to improve prognosis. The purpose of this study is to evaluate whether inhibition of ADAM17 sensitizes ovarian cancer to treatment with olaparib, a PARPi, thereby bypassing resistance mechanisms and improving treatment response. Thus, we analyzed the effect of olaparib in combination with the ADAM17 inhibitor GW280264X in ovarian cancer using a 2D monolayer and a 3D spheroid model followed by a multicontent readout (viability, caspase activation and cytotoxicity). To emphasize the translational aspect of our work, we performed corresponding experiments on primary cells derived from ovarian cancer patients initially screened for their mutation status of the breast cancer gene (BRCA 1/2). In 2D, we observed a significant reduction in cell viability and a subsequent increase in apoptosis of the combined treatment (olaparib + GW280264X) compared with olaparib mono-treatment. The combined treatment allows a substantial dose reduction of olaparib rendering a strong synergistic effect. Using a 3D spheroid model from primary cells, we confirmed the 2D monoculture results and demonstrated not only increased caspase activity under the combined treatment but also a substantial gain in cytotoxicity compared to the mono-treatment. Our study proposes ADAM17 inhibition sensitizing ovarian cancer to olaparib treatment and improving treatment response.